The Golem of Hollywood - Kellerman, Jonathan (G. P. Putnam's Sons, 2014)
Waking up beside a beautiful woman he has no memory of meeting, Detective Jacob Lev investigates a Hollywood Division murder case involving a severed head, an ominous message in Hebrew and the legend of the Golem of Prague.